Software Multimedia Para El Aprendizaje De Computación En El Cuarto Año De Educación Básica De La Escuela Republica Del Ecuador, De La Comunidad De Queseras Durante El Año Lectivo 2010- 2011 - Hinojoza Fernandez, Laura Beatriz (2011)
The present research work on "CREATING A MULTIMEDIA SOFTWARE COMPUTER LEARNING IN THE FOURTH YEAR OF BASIC EDUCATION SCHOOL" REPUBLIC OF ECUADOR, "CHEESE OF THE CANTON COMMUNITY Guaranda Bolivar province, during the school year 2010-2011. "has the sole purpose, constitute an alternative solution to such complicated difficulty presented in the Canton schools, especially in the fourth year of basic education in the area of computing, which detected a software that do not apply Multimedia learning strategies for computing, such as creative problem solving learning by teachers and adequately contribute to the development of skills and creative thinking skills making you more active and easier to study computer science and learning and achieve significant. For the development of research work is part of the background which is manifested in the school "Republic of Ecuador", which allowed us to identify the reality of an educational problem, that has not been time to raise awareness among teachers to achieve exceed the levels that we wished to study an innovative methodology as a software implementation of multimedia in teaching computer science. The identified problem occurs when the environment in which education develops children Quarter Year Basic Education School in research. The problem of the lack and importance of teachers in terms of learning technology, particularly through a multimedia software and troubleshooting computer's academic performance, this software is considered an educational effort, since the same is taught in theory and practice. It fully supports the work of a degree, indicating the importance, necessity, relevance, originality and feasibility and, according to the context in which development research work, of course obstinacy found the teacher to get information. This is understandable by the very fact that the issue is very important and needs the treatment and practice of teacher professionalism. According to these parameters raises the general and specific objectives, they have a high degree of validity, reliability and enforceability to achieve their scope and measuring, hypothesis testing, which allowed us to identify two variables that were operationalized appropriately according to their parameters. All this development have helped us Operationalizing the elements necessary for developing the tools of data collection. In Chapter I, theoretical framework, we describe issues directly related to the subject of the investigation, which are applicable in the course of Informatics, such as problem solving, and the principles of this strategy which will have a very special Scientific theory. In Chapter II, describes the methods that support for the organization and execution of this work, as well as methods that were practical, analytical, synthetic, inductive, historical and psychological, presented in an easy to follow, so which ultimately has a very practical level of appreciation and objective prior to determining the type of research, selection of the universe and the relationship established for the school applied to the research subjects, which was in full ( 2 teachers and 45 students) quantifiable population. Chapter III details the results obtained after the survey, which were tabulated in a thorough and configure them relevant charts and graphs, then interpret qualitatively analyzed. This allowed reaching the testing of the hypothesis and drawing our own conclusions on that basis and making our recommendations. Finally, in chapter IV of this research work is available to a proposal based on the results of the surveys was applied to teachers and students in which it was noted that it is necessary and important and relevant multimedia software solution problems specifically in the area of Informatics children of the fourth year of elementary school. As noted, this work investigates the reality is that the development of the subject classes in computing the Fourth Year Basic Education School "Republic of Ecuador". Not only establishes a diagnosis of this reality but also requires theoretical and practical problems and a proposal for the classroom, allowing effectively incorporate creative methods and techniques, so that students are active in its development and consequently, will become a critical input in their education and thus achieve meaningful learning.